2019
DOI: 10.3390/w11102168
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Current Situation and Prospects for the Development of Rainwater Harvesting as a Tool to Confront Water Scarcity Worldwide

Abstract: Nowadays, available water resources face severe pressures due to demographic, economic, social causes, environmental degradation, climate change, and technological changes on a global scale. It is well known that rainwater harvesting, a simple and old method, has the potential to supplement surface and groundwater resources in areas that have inadequate water supply. In recent decades, many countries have supported the updated implementation of such a practice to confront the water demand increase and to reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 26 publications
0
67
0
7
Order By: Relevance
“…Many researchers have confirmed that rain harvesting (RH) can provide water in urban/suburban, industrial, and rural areas [107][108][109][110][111][112][113][114][115][116][117][118], promising to save freshwater, a potential that may reduce tensions and competition among users. It is considered a low health risk, cost-efficient, and an environmentally friendly technology [119][120][121], a fact that has allowed its expansion in many developing and developed countries (EU, USA, UK, Japan, South Korea, Australia, and Africa) [116]. Experience indicates that RH requires advances in the domains of technology [116,122], urban and water planning [121,123], policy [116,124], assessment of economic impacts [125,126], and health risks [122].…”
Section: Use Of Non-conventional Water Resources As a Means To Mitigate Water Competitions And Conflictsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have confirmed that rain harvesting (RH) can provide water in urban/suburban, industrial, and rural areas [107][108][109][110][111][112][113][114][115][116][117][118], promising to save freshwater, a potential that may reduce tensions and competition among users. It is considered a low health risk, cost-efficient, and an environmentally friendly technology [119][120][121], a fact that has allowed its expansion in many developing and developed countries (EU, USA, UK, Japan, South Korea, Australia, and Africa) [116]. Experience indicates that RH requires advances in the domains of technology [116,122], urban and water planning [121,123], policy [116,124], assessment of economic impacts [125,126], and health risks [122].…”
Section: Use Of Non-conventional Water Resources As a Means To Mitigate Water Competitions And Conflictsmentioning
confidence: 99%
“…It is considered a low health risk, cost-efficient, and an environmentally friendly technology [119][120][121], a fact that has allowed its expansion in many developing and developed countries (EU, USA, UK, Japan, South Korea, Australia, and Africa) [116]. Experience indicates that RH requires advances in the domains of technology [116,122], urban and water planning [121,123], policy [116,124], assessment of economic impacts [125,126], and health risks [122].…”
Section: Use Of Non-conventional Water Resources As a Means To Mitigate Water Competitions And Conflictsmentioning
confidence: 99%
“…Rainwater harvesting (RWH) is an ancient water management practice, which was adopted mainly in arid and semi-arid areas of the world as a method for conservation, storage and distribution of fresh water for potable and non-potable use [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of RWH systems has been abandoned or reduced in the last century in recent years, in many parts of the world, there has been a renewed interest in rainwater collection techniques, as a sustainable source of water to meet domestic, irrigation and livestock water needs. This is related to the pressures on existing water resources by rising water demands due to climate variability, urbanization, and growing population, as well as increased food production [1,3]. In addition, the role of rainwater harvesting systems is important in flood mitigation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Rainwater harvesting increases water self-sufficiency and delays the need to build new centralized water infrastructure [3][4][5]. Globally implemented RWH systems could cover up to 90% of household water consumption [6] and the RWH plays a critical role in solving the world's problem of increased water stress [7,8]. Also, these systems can be useful in the reduction of flood risk in urban areas [9,10].…”
Section: Introductionmentioning
confidence: 99%